Phenotypic differentiation of Streptococcus intermedius, Streptococcus constellatus, and Streptococcus anginosus strains within the "Streptococcus milleri group". - Whiley, R A (1990)
A biochemical scheme was developed by which strains of Streptococcus constellatus, Streptococcus intermedius, and Streptococcus anginosus can reliably be distinguished from within the "Streptococcus milleri group." Strains identified as S. intermedius were differentiated by the ability to produce detectable levels of alpha-glucosidase, beta-galactosidase, beta-D-fucosidase, beta-N-acetylgalactosaminidase, beta-N-acetylglucosaminidase, and sialidase with 4-methylumbelliferyl-linked fluorogenic substrates in microdilution trays after 3 h of incubation at 37 degrees C, together with the production of hyaluronidase. Strains of S. constellatus and S. anginosus were differentiated by the production of alpha-glucosidase and hyaluronidase by the former and the production of beta-glucosidase by the latter. The majority of strains of the S. milleri group obtained from dental plaque were identified as S. intermedius, as were most strains isolated from abscesses of the brain and liver. Strains of S. constellatus and S. anginosus were from a wider variety of infections, both oral and nonoral, than were strains of S. intermedius, with the majority of strains from urogenital infections being identified as S. anginosus.